(untitled) (Research, Society and Development, 2020)
A drainage system must be dimensioned according to the design rainfall, being essential the choice of its measurement method to guarantee a safe, efficient and inexpensive design. Considering this, this research aimed to analyze three methods of estimating rainfall intensity considering the hydrological conditions of Marabá-PA, verifying which one is more compatible with the types of urban drainage. For that, it was compared IDF (Intensity-Duration-Frequency) curves elaborated from the methods of rain equations, Bell and Gumbel’s Disaggregation, the latter two being based on a hydrological data series of 46 years (1973-2018). The results showed that the rain equation method presents greater intensities for low recurrence periods, burdening microdrainage systems. For this type of drainage, it was found to be more rational to use intensities of rain using the Gumbel method. For macrodrainage, the values showed less discrepancy, however, there was more reasonableness in the use of the rain equation method and, in its absence, the Bell method. The methods showed excellent agreement with each other - they can be commonly compared for longer periods of rain. Thus, it was concluded to evaluate the conditions of duration and recurrence for the type of dimensioned urban drainage, in order to balance project intensities that mitigate the effects of burden and vulnerability to failures.